Single Tooth Implant Vs Non-Surgical Root Canal: Long-Term Survival Rates - Mahesh Suganna; Debkant Jena; Nidhi S. Jhala; Ranjita S. Baghel; Nahid Afzal; Shivani Singh (Journal of Pharmacy and Bioallied Sciences)
Introduction: Initial root canal treatment and the replacement of a single tooth with implants are both viable treatment options, but various success rates have been reported for each treatment modality. Materials and Methods: This study compared 145 implant and 176 root canal treatment teeth in patients for four possible outcomes- success, survival, and failure. Results: Outcomes were as follows for root canal treatment and implant outcomes, respectively: success 75.56% and 80.00%; survival 18.18% and 11.72%; and failure 6.25% and 8.27%. The location of the restoration in the mouth did not affect the outcome. Conclusion: This study suggests that restored endodontically treated teeth and single tooth implant restorations have similar failure rates, although the implant group showed a longer average and median time to function and a higher incidence of postoperative complications requiring subsequent treatment intervention.